Analysis of Clouding and Extinguishing Forest and Land Fires in Lumut Maju Village, Lumut Sub-district, Central Tapanuli Regency - Rahmawaty Rahmawaty; Sawal R Pulungan; Widya Natasha Napitupulu; Rolyn SDH Sinaga; Sylvia F Panjaitan; Young F Limbeng (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Forest and land fires are a recurring environmental threat in many parts of Indonesia. This study aims to analyze the level of fire vulnerability and the effectiveness of fire suppression efforts in Lumut Maju Village, Lumut Sub-district, Central Tapanuli Regency, North Sumatra Province. The analysis was conducted using a Geographic Information System (GIS)-based spatial approach with ArcGIS Software. The results indicate that most areas in Lumut Maju Village exhibit moderate to high levels of fire vulnerability, influenced by topographic conditions, land cover, human activities, and climatic factors. The implementation of fire suppression highlighted the importance of team preparedness, adequate equipment, and rapid response in controlling fires, despite challenges such as difficult terrain and limited water sources. GIS-based fire vulnerability mapping proved effective in supporting mitigation strategies and informed decision-making. Active community participation and strong coordination among stakeholders are essential to enhance sustainable forest and land fire prevention and control efforts.